Does the Attention of the Chinese Government Influence Chinese Nutrition, Exercise, and Health? Based on the Content Analysis of the Central Government Work Reports From 1978 to 2020 - Zhang, Wenpeng; Zhou, Yuomei; Li, Jingzhan; Zeng, Tingting; Liao, Jinlian (Frontiers in Nutrition, 2021)
The Chinese government’s attention on nutrition, exercise and health refers to the attention degree of Central Government to Chinese nationals’ nutrition, exercise and health, and reflects whether Central Government attach importance to Chinese nationals’ nutrition, exercise and health or not and the distribution of resources, which influences the physical quality and health level of Chinese nationals. Based on the attention theory and attention distribution proposed by Herbert Simon, Dai Kai, et al., the article took 43 Central Government Work Reports from 1978 to 2020 as research sample and used literature reviews and textual analysis methods, and applied Nvivo12.0 software to conduct qualitative and quantitative analysis about the contents of the Central Government Work Report concerning Chinese nationals’ nutrition, exercise and health. The research found that Central Government’s attention level to Chinese nationals’ nutrition, exercise and health has varied greatly between 1978 and 2020; On the whole, the attention and resources distributed by Central Government to Chinese nationals’ nutrition, exercise and health have been increasing; With Central Government’s increasing attention and resource distribution to Chinese nationals’ nutrition, exercise and health, the dietary structure of Chinese nationals were increasingly enriched and optimized, sports venues and exercise opportunities were gradually increased, and national health and life expectancy were continuously improved. This reflected that the improvement of Chinese nationals’ nutrition, exercise and health level attributed to the attention and support of Central Government.